2022
DOI: 10.1097/md.0000000000030221
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of the circRNA-miRNA-mRNA network for atrial fibrillation

Abstract: Atrial fibrillation (AF) is a chronic and progressive disease, with advancing age, the morbidity of which will increase exponentially. Circular ribonucleic acids (RNAs; circRNAs) have gained a growing attention in the development of AF in recent years. The purpose of this study is to explore the mechanism of circRNA regulation in AF, in particular, the intricate interactions among circRNA, microRNA (miRNA), and messenger RNA (mRNA). Three datasets (GSE129409, GSE68475, and GSE79768) were obtained from the Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Notably, upregulation of cXcR4 expression was observed in patients with atrial fibrillation (AF) a decade ago (48). Recently, a flurry of bioinformatics analyses of clinical high-throughput data sets revealed that cXcR4 is a potent hub gene strongly associated with the pathogenesis of AF (49)(50)(51)(52). Previous studies with a mouse model of AF suggested that cXcR4 antagonist AMd3100 can treat AF by ameliorating calcium mishandling and tissue inflammation (50,52).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, upregulation of cXcR4 expression was observed in patients with atrial fibrillation (AF) a decade ago (48). Recently, a flurry of bioinformatics analyses of clinical high-throughput data sets revealed that cXcR4 is a potent hub gene strongly associated with the pathogenesis of AF (49)(50)(51)(52). Previous studies with a mouse model of AF suggested that cXcR4 antagonist AMd3100 can treat AF by ameliorating calcium mishandling and tissue inflammation (50,52).…”
Section: Discussionmentioning
confidence: 99%
“…The advanced options were set as degree cutoff = 2, haircut, node score cutoff = 0.2, k-core = 2, and max depth = 100 [ 24 ]. In addition, hub genes in the PPI network were filtered by the Maximal Clique Centrality (MCC) arithmetic of the Cytoscape plug-in cytoHubba, which ranks nodes according to their attributes in the network, mining key genes (hub genes) and sub networks [ 25 , 26 ], the top ten nodes ranked by the MCC algorithm were considered as hub genes.…”
Section: Methodsmentioning
confidence: 99%
“…Using bioinformatics data to simplify the circRNA-miRNA-mRNA interactions, which are comprised of such complicated processes, can shed light on in vitro and in vivo investigations. For example, in the bioinformatics study of Liu et al [ 5 ], it was emphasized that hsa_circRNA_0003638 may play a role in the pathogenesis of atrial fibrillation by targeting the CXCR4 gene via hsa-miR-1207-3p. Similarly, Hu et al [ 6 ] suggested that the interaction of hsa_circ_0009581 / hsa-miR-150-5p , and hsa_circ_0001947 / hsa-miR-454-3p may play a role in the AML cancer process.…”
Section: Introductionmentioning
confidence: 99%